Multiple solution for a fourth-order nonlinear eigenvalue problem with singular and sublinear potential - FARKAS, Csaba; MEZEI, Ildikó Ilona; NAGY, Zsuzsánna-Tímea (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
Let (M, g) be a Cartan-Hadamard manifold. For certain positive numbers µ and λ, we establish the multiplicity of solutions. Mathematics Subject Classification (2010): 54AXX. Received 04 December 2022; Revised 08 February 2023. Published Online: 2023-03-20. Published Print: 2023-04-30